Barriers and strategies for cervical cancer screening: What do female university students know and want? - Hye Young Shin (Public Library of Science (PLoS), 2021)
Objective This study aimed to identify the distinct barriers and knowledge level of cervical cancer screening among female university students and establish intervention strategies to overcome these barriers. Methods This study used a mixed-methods design with 26 female university students aged 20-29 years. We first conducted a quantitative online survey for the same study participants, divided them into three groups, and conducted focus group interviews (FGIs). Group A: participants who had sexual experience and had undergone cervical cancer screening; Group B: participants who had sexual experience and had not undergone cervical cancer screening; Group C: participants who did not have sexual experience and had not undergone cervical cancer screening. Results The participants' ages were 21.92 ± 1.26 years. The knowledge levels for cervical cancer and screening were low to moderate. The four main themes that emerged as barriers to cervical cancer screening through the FGIs were: 1) socio-cultural barrier: conservative social perception of unmarried women's sexual life, 2) knowledge barrier: lack of knowledge and information, 3) psychological barrier: discomfort, and 4) practical barrier: time-consuming. The three themes identified for strategies were: 1) socio-cultural intervention: changing social perceptions and ensuring confidentiality, 2) educational intervention: improvement of knowledge and accessibility, and 3) alternative screening intervention: comfortable screening methods. Conclusions While university students' sexual experience rapidly increased, the socio-cultural perceptions of sexual health remained closed, and they had a reasonably low level of knowledge about cervical cancer screening. Therefore, various strategies sensitive to female university students' culture should be implemented to increase the knowledge level, and social efforts should be made to change the socio-cultural perception of unmarried young women's sexual health.